Freshwater vertebrate metabarcoding on Illumina platforms using double-indexed primers of the mitochondrial 16S rRNA gene - Vences, Miguel (2016)
Metabarcoding is a promising tool for biodiversity inventories and other applications in conservation genetics. We developed a new pair of primers for efficient and affordable high-throughput analysis of a 250 base pair stretch of DNA from the mitochondrial 16S rRNA gene of vertebrates, especially amphibians and fishes. By adapting a double-indexed protocol for Illumina platforms, our approach allows pooling of hundreds of samples in a single sequencing run. We obtained high detection rates of 82-93 % for fish in two German streams, 70 % for mock mixes of DNA from amphibians and fishes, and could distinguish multiple gene copies in amphibians, probably caused by nuclear-mitochondrial transposed DNA or heteroplasmy.